Re-Design Modern Industrial Workshop Table with Total Deformation Analysis and Stress Test - Juwitasari, Dhian; Kristianto, Fesa Putra; Fariz, Nuthqy (Universitas Insan Cendekia Mandiri, 2024)
Modern Industrial Workshop Table is a table used for the manufacture of furniture at the workshop site. Workshop tables are usually used to set furniture work ranging from light to heavy. Currently, workshop tables are not widely sold in the market, but workshop table users prefer to design and make their own. Therefore, the Polytechnic of Furniture and Wood Processing Industry (Polifurneka) designed its own workshop table. In designing a workshop table the factors of comfort and strength are the main ones. On the strength factor, the design of the workshop table can be tested with the help of ANSYS software version 18.1. The analysis aims to find out the stress, deformation and crack test. The simulation results with 400N, 500N, and 600N forces are the maximum equivalent stress of 1,4x10-6 Pa, 1,75x10-6 Pa, and 2,1 x10-6 Pa. Total deformation of 0,011m, 0,013m, and 0,015m. The conclusions of this study showed that the results of the first design had deformations in the leg supports of the table. Therefore, re-design is carried out so that there is no deformation and the maximum equivalent value of the new design stress is 1,12x10-6 Pa, 1,4x10-6 Pa, dan 1,69 x10-6 Pa. The total deformation of the new design 1,12x10-5m, 1,58x10-5m, dan 1,82 x10-5m. From the results of the re-design, it was found that the increase in the value of maximum equivalent stress and maximum principal stress, a decrease in total deformation, and did not show deformation on the table legs. Therefore, the latest Modern Industrial Workshop Table design was chosen for use in Polifurneka workshops.